Intervensi Anak Speech Delay Untuk Mengembangkan Kemampuan Bahasa Anak Usia Dini - Linda Miftahurrohmah; Pamuji Pamuji (Jurnal Ilmiah POTENSIA, 2024)
Research was conducted to identify problems in children development, one of which is children with speech delay in language development. this research discusses interventions carried out to overcome speech delay in children using several method. this research uses qualitative research by conducting observations and interviews with teacher and then observing children who experience speech delay. the result obtained were that children experienced speech delay with several indicators of languange developmet in children, especially children's speaking abilities experiencing delays, so intervention was carried out. the intervention carriend out on speech delay children showed that there was an increase in the child's speaking ability from not being able to become capable with the collaboration of parents and teachers as well as media support and repeated treatmen so as to develop the child's language skills